The Dynamics of Student Learning Behavior in the Implementation of the Merdeka Curriculum - Ach. Ubaidillah Al Jazili; Erfan Habibi; Nila Hanifiyah Hafid; Nuri Firdausiah (FKDP (Forum Komunikasi Dosen Peneliti), 2026)
This study examines the dynamics of student learning behavior in the implementation of the Merdeka Curriculum at MAN Bondowoso, focusing on cognitive, affective, and psychomotor aspects. Employing a qualitative approach with a descriptive case study design, data were collected through participant observation, in-depth interviews with 12 participants (vice principal for curriculum, Islamic Education teachers, general subject teachers, and students), and documentation study. Data analysis followed the interactive model of Miles, Huberman, and Saldaña. The findings reveal three main themes. First, in the cognitive aspect, differentiated and project-based learning enhanced students' conceptual understanding, critical thinking, and problem-solving skills. Second, in the affective aspect, the reinforcement of the madrasah's religious culture and teacher role modeling fostered disciplined, responsible, and enthusiastic learning attitudes. Third, in the psychomotor aspect, active engagement in P5 activities, entrepreneurship bazaars, digital presentations, and religious practices developed students' creativity and practical skills. The changes in learning behavior were intentional, positive-active, and effective-functional, characterized by self-aware learning, active participation, and the ability to apply learning outcomes in daily life. The study also identified challenges including uneven teacher readiness, dynamic classroom management, limited facilities, and adaptation of affective assessment systems. Limitations of this study include its single-case context, limited duration, and scope of perspectives that require further expansion. This research recommends comparative and longitudinal studies, as well as the development of affective and psychomotor assessment instruments for future research.